ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY PADA USAHA KECIL DAN MENENGAH (UKM) DODIK BAKERY - Abdurrahman Ahmad; Badrus Sholeh (Jurnal Riset Akuntansi Terpadu, 2019)
Inventory procurement raises other costs, ordering costs, compensation costs, maintenance costs, warehouse rental costs, and damage costs. Therefore, proper inventory management is needed to avoid increasing inventory costs and maximizing UKM (Small and Medium Enterprises) appropriately. The error of making decisions in the procurement of raw material inventories gives the impact of the number of finished goods not in accordance with market requirements. This study is conducted to determine the inventory control of raw materials and the comparison between the total costs of raw material inventory using the Dodik Bakery UKM policy using the Economic Order Quantity (EOQ) method. This research is a descriptive qualitative. Data collected by using library study methods and direct observation. The result of the study shows that the Economic Order Quantity (EOQ) method has more optimal and economical results compared to the method applied by the Dodik Bakery UKM. This is evidenced by the frequency of ordering with the Economic Order Quantity (EOQ) method which is less than 9 times, the difference is 88 times compared to the method used by Dodik Bakery SMEs as well as a lower inventory cost of Rp 1,992,492 compared to Rp 3,718,908 compared to the method used by UKM Dodik Bakery.